Effects of Cognitive Expectation on Sound-Induced Flash Illusion. (December 2019) - Wang, Aijun; Sang, Hanbin; He, Jiaying; Sava-Segal, Clara; Tang, Xiaoyu; Zhang, Ming
Sound-induced flash illusion (SIFI) is an auditory-dominated multisensory integration phenomenon in which flashes presented in conjunction with an unequal number of auditory sounds are illusorily perceived as equal in number to the auditory sounds. Previous studies on the factors that impact SIFI have mainly focused on top-down and bottom-up factors. This study aimed to explore the effects of top-down cognitive expectations on the SIFI by manipulating the proportion of trial types. The results showed that the accuracy of judgment was improved and reaction times were shortened when the instructions were consistent with the actual proportion of trial type. When the instructions were not consistent with the actual proportion of trial types, the instructions could still regulate the accuracy and reaction times in judging the fission illusion (i.e., a brief flash accompanied by two auditory stimuli tends to be perceived as two flashes) regardless of the actual proportion of trial types. The results indicated that top-down cognitive expectations could significantly reduce the fission illusion and accelerate the judgment, but the effect was not significant in the fusion illusion (i.e., two brief flashes accompanied by single auditory stimuli tend to be perceived as a single flash) due to the instability of the illusion.